Estrategias de publicidad y marketing de los emprendimientos de la Bahía de Babahoyo y el incremento de ventas - Cerezo Aviles, Yeiller Jacinto (2025)
Currently, the creation of businesses has become one of the most accessible forms of work for individuals and is a key element of economic growth. In the Babahoyo canton, entrepreneurship has had a considerable increase, motivated by the interest of obtaining income or the need to survive. For this reason, this research work focused on marketing and advertising strategies for the promotion of ventures so that they can remain in the market, differentiate themselves from the competition and increase sales and therefore grow in the future. The research approach is mixed, the type of research used was bibliographic. The methods used were inductive and descriptive. The technique used was the survey and documentary consultation, interview, observation. . . The population sample was 96 owners of the businesses in the Bay of the Babahoyo canton selected through the application of the formula. Furthermore, businesses in the Bay Area do not have successful growth, and they do not differentiate themselves from the competition due to the lack of implementation of a marketing and advertising strategy plan.